2002
DOI: 10.1002/jand.2002.23.1.84
|View full text |Cite
|
Sign up to set email alerts
|

Testosterone Release From a Subcutaneous, Biodegradable Microcapsule Formulation (Viatrel) in Hypogonadal Men

Abstract: Men with hypogonadism require testosterone replacement for optimal health. In the United States, testosterone is currently administered by daily transdermal patches, topical gels or intramuscular injections every 1-3 weeks. Biodegradable polylactideco-glycolide microcapsules are currently used for long-term drug delivery in humans. Such microcapsules that contain testosterone could provide a better means of long-term testosterone therapy. We therefore studied the pharmacokinetics and pharmacodynamics of testos… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2003
2003
2017
2017

Publication Types

Select...
6
3

Relationship

1
8

Authors

Journals

citations
Cited by 29 publications
(7 citation statements)
references
References 21 publications
0
7
0
Order By: Relevance
“…Each specimen was placed in a sealed polypropylene tube labeled with the study number and stored frozen (<210°C) until submitted (without further identification) for analysis of total testosterone (etherextracted) and estradiol by highly specific time-resolved fluoroimmunoassay (Delfia; Wallac Oy, Turku, Finland). 26 The lower limits of detection for testosterone and estradiol were 0.5 nmol and 50 pmol, respectively. Mean intraassay and interassay coefficients of variation were 3.1% and 4.5% for testosterone and 2.4% and 3.8% for estradiol.…”
Section: Serum Sample Collectionmentioning
confidence: 99%
“…Each specimen was placed in a sealed polypropylene tube labeled with the study number and stored frozen (<210°C) until submitted (without further identification) for analysis of total testosterone (etherextracted) and estradiol by highly specific time-resolved fluoroimmunoassay (Delfia; Wallac Oy, Turku, Finland). 26 The lower limits of detection for testosterone and estradiol were 0.5 nmol and 50 pmol, respectively. Mean intraassay and interassay coefficients of variation were 3.1% and 4.5% for testosterone and 2.4% and 3.8% for estradiol.…”
Section: Serum Sample Collectionmentioning
confidence: 99%
“…Testosterone therapy is a popular treatment for male hypogonadism humans (Jockenhövel, 2004). For instance, Amory et al (2002) reported that mean serum testosterone levels (726 pg/ml) peaked immediately following an injection of 6. 3 mg/d of testosterone.…”
Section: Effects Of Hay Bales and Perches On Broiler Behaviormentioning
confidence: 99%
“…98,99 In a US study of hypogonadal men, the effects of T micro 267 mg were evaluated for up to 8 weeks and 534 mg for up to 12 weeks. 100 T micro resulted in rapid and prolonged restoration of T to eugonadal levels, with C avg values of 413-522 ng/dl and a halflife of 20.4-22.3 days 100 over the dose range. Serum T peaked at 731 ng/dl on day 2 after the lower dose and at 995 ng/dl on day 1 after the higher dose.…”
Section: Potential Future Agentsmentioning
confidence: 93%
“…Serum T peaked at 731 ng/dl on day 2 after the lower dose and at 995 ng/dl on day 1 after the higher dose. 100 T micro significantly enhanced the quality and duration of erections, as well as relieving feelings of irritability from baseline. Treatment was well tolerated.…”
Section: Potential Future Agentsmentioning
confidence: 94%